Expression of a noncoding RNA is elevated in Alzheimer's disease and drives rapid feed-forward regulation of β-secretase - Faghihi, Mohammad Ali; Modarresi, Farzaneh; Khalil, Ahmad M; Wood, Douglas E; Sahagan, Barbara G; Morgan, Todd E; Finch, Caleb E; St. Laurent III, Georges; Kenny, Paul J; Wahlestedt, Claes (Nature medicine, 2008)
BACE is an enzyme necessary for the generation of neurotoxic amyloid-β in Alzheimer's disease. Claes Wahlestedt and his colleagues identify a noncoding RNA that is upregulated in the brains of individuals with Alzheimer's disase. This noncoding RNA increases expression of BACE, driving amyloid-β generation and possibly disease progression. Recent efforts have revealed that numerous protein-coding messenger RNAs have natural antisense transcript partners, most of which seem to be noncoding RNAs. Here we identify a conserved noncoding antisense transcript for β-secretase-1 ( BACE1 ), a crucial enzyme in Alzheimer's disease pathophysiology. The BACE1-antisense transcript ( BACE1 -AS) regulates BACE1 mRNA and subsequently BACE1 protein expression in vitro and in vivo . Upon exposure to various cell stressors including amyloid-β 1–42 (Aβ 1–42), expression of BACE1 -AS becomes elevated, increasing BACE1 mRNA stability and generating additional Aβ 1–42 through a post-transcriptional feed-forward mechanism. BACE1 -AS concentrations were elevated in subjects with Alzheimer's disease and in amyloid precursor protein transgenic mice. These data show that BACE1 mRNA expression is under the control of a regulatory noncoding RNA that may drive Alzheimer's disease–associated pathophysiology. In summary, we report that a long noncoding RNA is directly implicated in the increased abundance of Aβ 1–42 in Alzheimer's disease.